Effects of Pain Reduction by Self-Natural Posture Exercise on Affective Complexity in Women: The Moderating Effect of Self-Regulation - Choi, Jungki; Yoon, Jiyoo; Shin, Myoungjin (Frontiers in Psychology, 2020)
This study aimed to investigate the effects of pain reduction and self-regulation efficacy on affective complexity in female patients with chronic pain after participation in an exercise therapy program—Self-Natural Posture Exercise (SNPE)—within the theoretical framework of the Dynamic Model of Affect. A 12-week SNPE program (thrice a week, 70 min per session) was conducted with 101 women with chronic pain lasting longer than 6 months. Pre- versus post-SNPE difference in the correlation between positive affect (PA) and negative affect (NA) was examined through Fisher’s z test, and the moderation effect was confirmed through hierarchical regression analysis. Upon completion of the program, participants experienced pain [Mpre = 5.68 (SDpre = 1.96) vs. Mpost = 3.12 (SDpost = 2.16)] and stress reduction [Mpre = 2.92 (SDpre = 0.95) vs. Mpost = 2.62 (SDpost = 0.86)], higher satisfaction with life [Mpre = 4.25 (SDpre = 1.20) vs. Mpost = 4.80 (SDpost = 1.15)], and decreases in the negative correlation between PA and NA (rpre = −0.541 vs. rpost = −0.379). Furthermore, participation in the SNPE program neutralized the impact of PApost on NApost (β = −0.03) in participants with high self-regulation and pain reduction. These results suggest that self-regulation helps to increase SNPE adherence, which would induce pain reduction and restore affective complexity. Based on the strength model of self-control, to increase the pain reduction through exercise therapy, the instructor should ensure that the participants are not being ego depleted.